2016
DOI: 10.1287/mnsc.2015.2204
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Pooling Under Heavy-Tailed Demand

Abstract: Risk pooling has been studied extensively in the operations management literature as the basic driver behind strategies such as transshipment, manufacturing flexibility, component commonality, and drop-shipping. This paper explores the benefit of risk pooling in the context of inventory management using the canonical model first studied in Eppen (1979). Specifically, we consider a single-period multi-location newsvendor model, where n different locations face independent and identically distributed demands and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 36 publications
0
38
0
1
Order By: Relevance
“…In another study, Gaffeo, Scorcu and Vici [20] analyzed the demand of books in Italy and found that for the three categories -local novels, foreign novels and non-fiction books, a power law distribution where the exponent is typically lesser than 2 is a good fit to the right tail of the demand distribution. Bimpkis and Markakis [8] used the ratings of movies on Netflix as an approximation to the demand of a movie and estimated a power law distribution with an exponent of around 1.04 for the number of movies per number of distinct ratings. Using data from a North American retailer over a one year period with 626 products, their statistical tests showed that the exponential and normal distributions were a poor fit to the data while the power law provided a reasonable approximation to the dataset.…”
Section: Empirical Evidence Of Heavy Tailed Demandmentioning
confidence: 99%
“…In another study, Gaffeo, Scorcu and Vici [20] analyzed the demand of books in Italy and found that for the three categories -local novels, foreign novels and non-fiction books, a power law distribution where the exponent is typically lesser than 2 is a good fit to the right tail of the demand distribution. Bimpkis and Markakis [8] used the ratings of movies on Netflix as an approximation to the demand of a movie and estimated a power law distribution with an exponent of around 1.04 for the number of movies per number of distinct ratings. Using data from a North American retailer over a one year period with 626 products, their statistical tests showed that the exponential and normal distributions were a poor fit to the data while the power law provided a reasonable approximation to the dataset.…”
Section: Empirical Evidence Of Heavy Tailed Demandmentioning
confidence: 99%
“…Stable distributions represent a broad family that subsumes many distributions frequently used by academics and practitioners, such as Gaussian, Cauchy, and Lévy, which can be tailored in terms of their mean, scale, skewness, and tail asymptotics. Importantly, the stable class includes both light-tailed and heavy-tailed distributions, capturing fundamentally different demand variability regimes; for further discussion and empirical evidence of heavy-tailed demand uncertainty see Bimpikis and Markakis [2016]. We restrict attention to symmetric stable distributions that have a well defined mean, which we also assume to be high enough so that the probability of negative demand is negligible, i.e., F i (0) ≈ 0, i = 1, 2.…”
Section: Modelmentioning
confidence: 99%
“…They revealed that the profit gain by inventory pooling is strongly affected by the tail dependence between products. Bimpikis and Markakis (2014) studied the inventory pooling problem under heavy-tailed demand. They showed that the benefit from pooling decreases as the tail of demand becomes heavier.…”
Section: Literature Reviewmentioning
confidence: 99%